La colonisation du Viet Nam et le colonialisme vietnamien - Vuong, Thanh (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1987)
To attack the rules is to outmaneuver the friends and foes at the lower level of the game of policies and alliances. The rules are at the higher level of the context of that game, the historical and cultural context of warring Viet Nam. What makes Viet Nam unique is its social organization based on a loosely knitted network of villages through deep and strong relations capable of repelling intruders and invading neighbors, both moving and still like the moon underneath. Here, the chinese civilization has made a new nation assimilating the model and resisting the domination. Elsewhere, the be same chinese civilisation has made another chinese provinces. History of Viet Nam is written by an advancing front of modest and primitive villages from a delta to the next, from the gulf of Tonkin to the gulf of Siam, « vietnamizing » the nature and the peoples on its passage by the plow and the sword. South Viet Nam was cambodian land a century ago and the french colonial administration put an end to the siamese-vietnamese « condominium » over Cambodia after a short 0 to 0 fight between Siam and Viet Nam, the first claiming its western part of the vietnamese colony de facto and de jure. Cambodia was then ruled by a vietnamese general governor assisted by two lieutenant governors. The present vietnamese occupation of Cambodia, in this perspective, may be both a « prelude » to the continuation of this advancing front of villages, the confrontation between Viet Nam and Thailand (fancy and hegemonostic name for Siam since 1939) for the leadership of South East Asia and a « fugue » for warring Viet Nam to solve its political and economical problems, a country and people forged in war and for war during these four decades. The vietnamese claim of the Mekong river as a link may be translated in german word as « Anschluss » or reunification.